High rate of complications in patients with carcinoma of the cervix surgically treated after radical radiotherapy - Fras, Albert-Peter (Radiology and oncology (Ljubljana), 1995)
With the aim to improve the results of treatment of patients who had advanced carcinoma of the uterine cervix and were radically irradiated, a group of 49 patients underwent hysterectomy two to 24 months after completion of radiotherapy, among whom for only 43 patients data were available. Radiotherapy consisted of 40 Gy external beam irradiation to true pelvis, low dose intracavitary treatment to a total dose 40 Gy to point A, and parametrial irradiation 16 to 20 Gy, shielding the place where radioactive sources were positioned during intracavitary therapy. Necrosis, persistent cervical carcinoma, recurrent carcinoma, and in patients younger than 50 years no evidence of disease (NED) with dysplasia were indications for the surgical treatment. Hysterectomy with bilateral oophorectomy was as conservative as possible but severe complications, such as ureteral stenosis (five cases), recto-vaginal fistula (three cases), vesico-vaginal fistula (two cases), recto-vesico-vaginal fistula (one case) occurred. Asymptomatic frozen pelvs as a mild complication occurered in 10 cases. One patient died postoperatively because of dehiscence and abdominal wall necrosis. In 17 (39.5%) of 43 patients complications occurred, although asymtomatic frozen pelvic was not taken in account. We believe that such a combined treatment is only for selected cases.
Keywords: Cervix neoplasms; Complications; Hysterectomy; Postoperative period; Radiotherapy; Surgery